Stars and other signs : poems - Borroff, Marie (Yale University Press, 2002)
These poems, written over fifty years, address such subjects as the celerity of time, old age, art, literary acquaintances, and the author's beloved New England landscape. They delight in sound and form, even as they unsettle and disturb.